Collective absolution of many penitents without prior individual confession in case of grave necessity (can. 961 § 1 No. 2 and § 2 of the Code of Canon Law) - Adamczyk, Jerzy (Prawo Kanoniczne, 2021)
The purpose of the article is to show the issue of collective absolution of many penitents without prior individual confession in case of grave necessity. General absolution is an extraordinary way of reconciliation with God. In the first part are presented conditions for serious necessity regarding general absolution. The second part shows the person of the diocesan bishop, who is entitled to state that conditions of serious necessity for collective absolution exist or do not exist, while the third part is devoted to the norms of episcopal conferences on collective absolution in cases of serious necessity. The whole article ends with conclusions and bibliography.